Organizational sustainability and employee retention: the role of workplace spirituality in rural banks - Fahmy Akbar Idries; Suhada Suhada; Novi Diah Wulandari; Zulfatun Ruscitasari; Atik Widia Rahayu (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2026)
Employee retention is crucial for organizational sustainability, especially in rural banking institutions, where human capital is vital to performance. This study explores the impact of perceived organizational sustainability (POSu) on employee retention intention (RI), with workplace spirituality (WS) mediating the relationship, as viewed through the lens of Social Exchange Theory. A quantitative survey was conducted among marketing employees in Indonesia’s Rural Banks (Bank Perkreditan Rakyat). The findings revealed that while POSu did not directly affect retention intentions, WS had a direct influence and enhanced this relationship by promoting a sense of meaningful work and belonging. These results underscore the need to boost employees' perceptions of organizational sustainability and cultivate workplace spirituality to improve retention intentions, thereby contributing to the literature on employee retention in rural banking contexts.